Environment and economy based optimization of CWS featured air coolers. (1st October 2019) - Qi, Zefeng; Ma, Yifan; Chen, Chuang; Wang, Yufei; Feng, Xiao
Abstract: Cooling water system (CWS) is a very common system that discharges industrial waste heat. For the existing researches about industrial CWSs, most of them focus on economic performance, ignoring the environmental impact. Based on the industrial foundation, this work proposes a methodology to optimize and evaluate the economic performance and environmental impact. This paper integrates several components, such as cooler network, pump network, cooling tower and air cooler to optimize the total annual cost. Carbon footprint and water footprint are introduced as environmental indicators. The whole system is integrated into Mixed Integer Nonlinear Programming (MINLP) model and solved by GAMS. Through case study, an improved CWS structure chart is obtained, and the relationship between carbon footprint, water footprint and economic performance is drawn, showing the trade-off between the three. The result shows that total annual cost (TAC) can be reduced by 9.84% by economic optimization design. The result also gives a guideline on how to improve environmental performance according to water footprint and carbon footprint. Graphical abstract: Image 109077 Highlights: Structure of cooler network is optimized together with air coolers and pump network. Two environmental indicators are applied to evaluate the performance cooling water system. Cooling water system is optimized under different objectives. The relationship between economic performance and environmental impact is revealed.